Stability Analysis of SIR Mathematics Model in Shopeepay Later Addiction Case - Basir, Choirul; Salma, Anca Almira; Rahmat, Usep (Universitas Wiralodra, 2024)
This research discusses the case of Shopeepay Later addiction using the SIR mathematics model. Therefore, the purpose of this research is to build, analyze and find out the basic reproduction number (????0) and simulation of the SIR model of Shopeepay Later addiction. The research begins by building the assumptions of the SIR model of Shopeepay Later addiction, finding the equilibrium point, analyzing the stability of the equilibrium point using the jacobian matrix, finding the basic reproduction number (????0), and doing a simulation using Google Colab. The parameters used in this SIR model include the transmission rate parameter (????), the recovery rate parameter (????) the self-control parameter (????1), the promotion parameter (????2), and the application stop parameter (????3). The result of this study obtained the SIR model of Shopeepay Later addiction, one endemic equilibrium point is stable and the basic reproduction number ????0 = −37,29 that is, there is no transmission. Then to get expected conditions from the simulation result, namely given parameter values ???? = 0.5, ???? = 0.4, and ????1, ????2, ????3 = 0.9.